Exploring Helianthus Species for Resilience to Drought During the Critical Reproductive Stage - Jelena Jocković; Nada Grahovac; Željko Milovac; Milan Jocković; Siniša Jocić; Ana Marjanović Jeromela; Sandra Cvejić (Plants)
Drought stress during the reproductive phase of sunflower can significantly reduce achene yield by affecting inflorescence size, nectar quality, and pollinator activity. This study aimed to analyze the morphological characteristics of the reproductive region, quantify nectar sugar components, and evaluate pollinator presence and pollination success in wild Helianthus species as an important genetic resource for breeding cultivated sunflowers under drought conditions. Morphological investigations were conducted during the flowering and achene development phases with a stereo microscope and calipers. Nectar sugar concentrations were analyzed via HPLC, and pollinator presence was monitored twice a week for two months. This study highlights the correlation between evaluated traits, emphasizing their importance as yield indicators. Significant differences were observed in reproductive characters, nectar quality, and pollination success among the species. Helianthus annuus and Helianthus argophyllus exhibited superior reproductive performance with high nectar sugar concentrations and larger inflorescences, enabling successful pollination and higher achene yield. In contrast, Helianthus debilis demonstrated lower reproductive efficiency, with a higher percentage of empty achenes. These findings provide valuable insights for breeding programs, highlighting H. argophyllus and H. annuus as promising genetic resources for developing sunflower genotypes with increased yield and improved floral traits adapted to drought conditions.